Experimental modal analysis in research - Żółtowski, Mariusz; Napieraj, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
Experimental modal analysis has grown steadily in popularity since the advent of the digital FFT spectrum analyser in the 1970’s. This days impact testing has become widespread as a fast and economical means of finding the vibration modes of a machine or structure. Its significantly use ascending roles can be seen also in the civil engineering industry [6]. This paper reviews the main topics associated with experimental modal analysis including making FRF measurements, modal excitation techniques, and modal parameter estimation from a set of FRFs.